Brazilian Network for Gestational Trophoblastic Disease Study Group Consensus on Management of Gestational Trophoblastic Disease - Braga, Antonio; Souza, Priscila Oliveira de; Vieira dos Santos Esteves, Ana Paula; Padron, Lilian; Uberti, Elza; Viggiano, Mauricio; Sun, Sue Yazaki; Maesta, Izildinha; Elias, Kevin M.; Horowitz, Neil; Berkowitz, Ross; Brazilian Network Gestational Trop (Sci Printers & Publ Inc, 2018)
OBJECTIVE: To present the Brazilian Network for Gestational Trophoblastic Disease Study Group consensus on management of gestational trophoblastic disease (GTD). STUDY DESIGN: The modified Delphi technique was used in this study to obtain a consensus among Brazilian specialists on the treatment of GTD. For the 64 statements listed, each participant was asked to assign a Likert scale value according to their agreement. The RAND/UCLA method was used to define the level of consensus among the specialists. RESULTS: The response rate of the potential study participants after the 2 rounds was 40/47 (85%). Of the 64 statements presented, there was an agreement on 54/64 (84%). The situations of disagreement were as follows: 1/12 (8%) statements in the section on diagnosis of GTD, 5/10 (50%) statements in the section on treatment of hydatidiform mole (HM), 2/16 (12.5%) statements in the section on diagnosis of gestational trophoblastic neoplasia (GTN), 1/14 (7%) statements in the section on treatment and follow-up of GTN, and 1/5 (20%) statements in the section on appropriate time to allow pregnancy after HM and GTN. CONCLUSION: This guideline will serve to standardize the conduct among the Brazilian GTD reference centers as well as to guide the new specialized services that may arise and eventually to physicians who may need to treat cases of GTD.
Keywords: Brazil; hydatidiform mole; gestational trophoblastic disease; rare cancers